2016
DOI: 10.1186/s12915-015-0223-4
|View full text |Cite
|
Sign up to set email alerts
|

The Sinocyclocheilus cavefish genome provides insights into cave adaptation

Abstract: BackgroundAn emerging cavefish model, the cyprinid genus Sinocyclocheilus, is endemic to the massive southwestern karst area adjacent to the Qinghai-Tibetan Plateau of China. In order to understand whether orogeny influenced the evolution of these species, and how genomes change under isolation, especially in subterranean habitats, we performed whole-genome sequencing and comparative analyses of three species in this genus, S. grahami, S. rhinocerous and S. anshuiensis. These species are surface-dwelling, semi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
301
2
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 292 publications
(323 citation statements)
references
References 77 publications
18
301
2
2
Order By: Relevance
“…Among differentially expressed APA transcripts, 21 are found in the testes, 18 in the liver and 11 in the brain. Recently, it has been shown that APA regulation is important for RNA processing during spermatogenesis (93). We compared APA transcripts with published datasets derived from different testis cell types (87) and found that the Cd68 APA transcript has altered 3′UTR.…”
Section: Resultsmentioning
confidence: 99%
“…Among differentially expressed APA transcripts, 21 are found in the testes, 18 in the liver and 11 in the brain. Recently, it has been shown that APA regulation is important for RNA processing during spermatogenesis (93). We compared APA transcripts with published datasets derived from different testis cell types (87) and found that the Cd68 APA transcript has altered 3′UTR.…”
Section: Resultsmentioning
confidence: 99%
“…As far as we know, this is the first report about the reference gene selection in Sinocyclocheilus fishes. The species in this genus were served as an emerging cavefish model (Yang et al, 2016) that it can be expected more and more researches were conducting to this group of fishes in the future. As a natural group of tetraploid fishes, designing appropriate primers for distinguishing different copies was the very fundamental step before the qRT-PCR analyses.…”
Section: Discussionmentioning
confidence: 99%
“…It has now been categorized as a second-class, state protected animal due to a dramatic population decrease by human activities (Pan et al, 2009). In the recent decade, the artificial breeding of this fish had been succeeded (Yang et al, 2007) and many other following studies were also conducted, such as the aquaculture management and conservation (Pan et al, 2010;Pan et al, 2011), the wholegenome sequencing (Yang et al, 2016) and etc. But up to now, gene expression research on this fish is still blank.…”
Section: Introductionmentioning
confidence: 99%
“…The genus Sinocyclocheilus (in the order of the Cypriniformes) contains at least 10 cavefish species. The availability of many closely related surface-dwelling species makes it a good model to study cave adaptation in an evolutionarily distant system from Astyanax mexicanus (which is found in the order of the Characiformes) [6,68]. Both orders share a common ancestor approx.…”
Section: Work On Other Cavefish Speciesmentioning
confidence: 99%
“…Worldwide, more than 150 species of obligate cavefish are described, endemic to all continents except Europe and Antarctica. The Northern cavefish Amblyopsis spelaea [3], the Somali cavefish Phreatichthys andruzzii [5], or the Chinese cavefish Sinocyclocheilus [6] are a few of the better-known species complementing work on Astyanax mexicanus. The cave forms of A. mexicanus are found in the Sierra del Abra of Northeastern Mexico in 29 known caves.…”
Section: Introductionmentioning
confidence: 99%